Phytochemical analysis of leaf extracts of antihyperglycemic medicinal plants - KUMARI SMITA; S. K. SARANGI; K. MANJUNATH (International Journal of Pharma and Bio Sciences, 2017)
Primary screening of phytochemicals is a crucial step, in the detection of the bioactive compounds present in medicinal plants and consequently may lead to drug discovery and development. In the present study, important phytoconstituents of the selected medicinal plants Ocimum canum (O. canum) and Costus igneus (C. igneus), were reported in order to relate their presence with bioactivities of the plants. Three different solvents namely n-hexane, ethylacetate and methanol according to their increasing polarity were used for extraction of phytoconstituents from the leaf part of both the plants. Qualitative phytochemical analysis of leaf extract was performed for the presence of triterpenoids, tannins, glycosides, sterols, alkaloids, flavonoids, carbohydrates, proteins and organic acids. Further quantitative analysis was conducted to determine the amount of total phenolics, total flavonoids, total alkaloids and total antioxidant activity of the phytocostituents. There was significant difference between the presence and absence of different phytocompounds in various leaf extracts. The total phenolics content was found to be maximum in the methanolic extracts of both the plants. The total flavonoid content was found to be maximum in the hexane extract of O. canum and ethylacetate extract of C. igneus. Furthermore, the total antioxidant capacity of O.canum was found to be higher than C. igneus